‘BeYOUtiful 2016’ HELPS INSTILL AWARENESS THAT EVERYONE IS UNIQUE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 15 November 2016 – The BeYOUtiful 2016 Project, organised by a group of finalyear students from the Universiti Sains Malaysia (USM) School of Communication is seen as being able to raise the awareness in society, that every individual is unique regardless of race, gender or social status.